Integrated Forensic Training Program for Indonesian National Police Investigators in West Java Region - Amri, Afdhal; Harun, Rahmah; Rahmad (Warta Pengabdian Andalas, 2026)
The increasing complexity of criminal cases in West Java necessitates a critical upgrade in the competency of Indonesian National Police (Polri) investigators regarding the application of Scientific Crime Investigation (SCI) principles. A significant gap has been identified in the integrated forensic evidence handling skills (digital, biological, and chemical) at the Sub-Regional Police Resort (Polres) level, potentially compromising the accountability of criminal proceedings. This training program aimed to enhance the capacity of 40 investigators from the Jabar region through a comprehensive, integrated forensic training course. The 5-day program (September 15-19, 2025) was conducted in collaboration with the National Police's Forensic Laboratory Center (Puslabfor Bareskrim Polri), utilizing a Pretest-Posttest design and a hands-on simulation methodology. Evaluation results demonstrated an average competency score increase of 48.57% (from 55.8 to 82.9), significantly exceeding the minimum target of 25%. The most drastic improvement was observed in the Digital Forensics module (79.57%). Practically, 92.5% of participants showed enhanced technical proficiency in applying the integrated Chain of Custody (CoC) protocol. The participant satisfaction level reached 94% (4.7 out of 5.0). This training proved highly effective in bridging the competency gap, strengthening science-based investigative administration, and supporting the establishment of an accountable criminal justice system. The adoption of technical guidelines and the implementation of a sustained program are recommended for follow-up.